Bom Bunuh Diri dalam novel Junūdullah, karya Fawwaz Haddad: Studi analisis Altruism Suicide Emile Durkehim. - Rasyad, Munawir (Universitas Muhammadiyah Gorontalo, 2023)
This study uses Emile Durkheim's theory of concepts altruism suicide as a basis for understanding the motive behind the act of suicide bombing in the novel